Modeling and Implementation of the Village Secretary Accounting Information System based on BPMN - Mayasir Aziza; Jaswadi Jaswadi; Nur Indah Riwajanti (PT. EQUATOR SINAR AKADEMIA, 2022)
This research is applied research that aims to improve the internal control of village financial management by implementing the modeling of the Village Secretary Accounting Information System based on the Business Process Modeling Notation (BPMN). Clean, effective, transparent, and accountable village financial management in Indonesia is currently not guaranteed because the Electronic-Based Government System has not been fully implemented. Village financial management accountability is the main topic discussed today because it relates to global development goals to achieve prosperity. The Village SDGs are a sustainable development goal that must achieve by 2030. Minister of Home Affairs Regulation Number 20 of 2018 concerning village financial management encourages villages to implement internal control in village financial management. This research uses the policy research method. The results showed what could apply the policy of using the Village Secretary Accounting Information System modeling based on the Business Process Modeling Notation (BPMN) in Wajak Lor Village. This research is limited to implementing the Village Secretary Accounting Information System modeling based on the Minister of Home Affairs Regulation Number 20 of 2018 concerning village financial management. Suggestions for further research are expected to be able to develop an Accounting Information System for village financial management based on Business Process Modeling Notation and develop village financial management applications that can be operated by the Village Secretary and integrated.